Prevalence and predictors of poor outcome in children with febrile neutropaenia presenting to the emergency department. (13th April 2022) - Long, Elliot; Babl, Franz E; Phillips, Natalie; Craig, Simon; Zhang, Michael; Kochar, Amit; McCaskill, Mary; Borland, Meredith L; Slavin, Monica A; Phillips, Robert; Lourenco, Richard De A; Michinaud, Francoise; et al.
Abstract: Objective: Children with acquired neutropaenia due to cancer chemotherapy are at high risk of severe infection. The present study aims to describe the prevalence and predictors of poor outcomes in children with febrile neutropaenia (FN). Methods: This is a multicentre, prospective observational study in tertiary Australian EDs. Cancer patients with FN were included. Fever was defined as a single temperature ≥38°C, and neutropaenia was defined as an absolute neutrophil count <1000/mm 3 . The primary outcome was the ICU admission for organ support therapy (inotropic support, mechanical ventilation, renal replacement therapy, extracorporeal life support). Secondary outcomes were: ICU admission, ICU length of stay (LOS) ≥3 days, proven or probable bacterial infection, hospital LOS ≥7 days and 28‐day mortality. Initial vital signs, biomarkers (including lactate) and clinical sepsis scores, including Systemic Inflammatory Response Syndrome, quick Sequential Organ Failure Assessment and quick Paediatric Logistic Organ Dysfunction‐2 were evaluated as predictors of poor outcomes. Results: Between December 2016 and January 2018, 2124 episodes of fever in children with cancer were screened, 547 episodes in 334 children met inclusion criteria. Four episodes resulted in ICU admission for organ support therapy, nine episodes required ICU admission, ICU LOS was ≥3 days in four, hospital LOS was ≥7 days in 153 and two patients died within 28 days. Vital signs, blood tests and clinical sepsis scores, including Systemic Inflammatory Response Syndrome, quick Sequential Organ Failure Assessment and quick Paediatric Logistic Organ Dysfunction‐2, performed poorly as predictors of these outcomes (area under the receiver operating characteristic curve <0.6). Conclusions: Very few patients with FN required ICU‐level care. Vital signs, biomarkers and clinical sepsis scores for the prediction of poor outcomes are of limited utility in children with FN. Abstract : Children receiving cancer chemotherapy who present to the ED with febrile neutropaenia are a high‐risk patient group. Using current care pathways, poor outcomes in this population are very rare, and prediction of poor outcomes is therefore difficult.